Peningkatan Profesionalitas Guru dalam Memotivasi Belajar Melalui Konseling Kelompok Behavior di UPTD SDN Gunung Rancak 3 Kecamatan Robatal Kabupaten Sampang Tahun Pelajaran 2019/2020 - Wiyadi Wiyadi (Journal on Education, 2023)
The results of observations found that many UPTD students at SDN Gunung Rancak 3, Robatal Sampang District had low learning motivation, this can be seen from the attitudes and behavior of students who are lazy to study, often do not do assignments/homework, do not pay attention to lessons, are not serious and do not concentrate, like to be busy in class, often skipping certain lessons, often skipping lessons, which in turn has an impact on low daily test scores or poor achievement. Data collection tools and techniques in the development of this counseling model are interview guidelines for interviewing students and teachers, observation guidelines for observing during the group counseling process and questionnaires for collecting data on student motivation. Observations in the field show that many students have low learning motivation, this is because they have maladaptive behavior (problematic behavior). For this reason, it is necessary to look for a counseling approach that can change students' adaptive malbehavior, namely the behavioral approach. Counselors need to learn a lot, both from literature, upgrading, workshops so that they can improve their ability to provide the right services for their students.